1998
DOI: 10.1097/00005721-199807000-00005
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Intervention to Promote Coping in Rural Teens

Abstract: School-based nurses are in an ideal position to provide assessment, referral, and intervention programs in the natural setting of the school. Results of this study indicate that such programs can be implemented successfully in schools and have the potential to promote mental health in teenagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 7 publications
4
44
0
Order By: Relevance
“…This included two systematic reviews (Tilley andChambers, 2003, Wainwright et al, 2000), nine RCTs (Cameron et al, 1999, DeLago et al, 2001, Harrell et al, 1998, Hill et al, 1991, Lamb et al, 1998, Persaud et al, 1996, Puskar et al, 2003, Werch et al, 1996, Werch et al, 2003, one quasi RCT where allocation was by coin toss (Pike and Banoub-Baddour, 1991) and four non-randomised controlled trials (Allen, 2003, Long et al, 1975, Munodawafa et al, 1995, Skybo and Ryan-Wenger, 2002). …”
Section: Current Evidence Base For School Nursing Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This included two systematic reviews (Tilley andChambers, 2003, Wainwright et al, 2000), nine RCTs (Cameron et al, 1999, DeLago et al, 2001, Harrell et al, 1998, Hill et al, 1991, Lamb et al, 1998, Persaud et al, 1996, Puskar et al, 2003, Werch et al, 1996, Werch et al, 2003, one quasi RCT where allocation was by coin toss (Pike and Banoub-Baddour, 1991) and four non-randomised controlled trials (Allen, 2003, Long et al, 1975, Munodawafa et al, 1995, Skybo and Ryan-Wenger, 2002). …”
Section: Current Evidence Base For School Nursing Interventionsmentioning
confidence: 99%
“…Ten studies were done in the USA (Allen 2003, DeLago 2001, Harrell 1998, Lamb 1998, Long 1975, Puskar 2003, Persaud 1996, Skybo 2002, Werch 1996, Werch 2003, two in Canada (Cameron et al, 1999, Pike andBanoub-Baddour, 1991), one in the UK (Hill et al, 1991) and one in Zimbabwe (Munodawafa 1995). Neither of the systematic reviews found any studies that met their inclusion criteria.…”
Section: Current Evidence Base For School Nursing Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of quasi-experimental designs initially used convenience samples, in which participants were then randomly assigned to either an intervention or control group (Bryan & Cook, 1967;Cameron et al, 1999;Chen et al, 1991;Ferson et al, 1995;Kimel, 1996;Lamb et al, 1998;Larsson & Carlsson, 1996;Long et al, 1975;Persaud et al, 1996;Werch et al, 1996). Analyses focused on the differences between the control and experimental groups.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Several of the frameworks complemented each other, such as individual counseling, focused intervention, and concentrated nursing services (Bryan & Cook, 1967;Chen et al, 1991;Long et al, 1975); the Health Belief Model and Jerrett and Costello's model of illness (Perry & Toole, 2000;Werch et al, 1996); and age/ developmental strategies (Coleman & Hawkins, 1970;Lamb et al, 1998).…”
Section: Conceptual Frameworkmentioning
confidence: 99%